Simultaneous observations of atmospheric tides from combined in situ and remote observations at Mars from the MAVEN spacecraft. Issue 4 (8th April 2016) - England, Scott L.; Liu, Guiping; Withers, Paul; Yiğit, Erdal; Lo, Daniel; Jain, Sonal; Schneider, Nicholas M.; Deighan, Justin; McClintock, William E.; Mahaffy, Paul R.; Elrod, Meredith; Benna, Mehdi; et al.
Abstract: We report the observations of longitudinal variations in the Martian thermosphere associated with nonmigrating tides. Using the Neutral Gas Ion Mass Spectrometer (NGIMS) and the Imaging Ultraviolet Spectrograph (IUVS) on NASA's Mars Atmosphere and Volatile EvolutioN Mission (MAVEN) spacecraft, this study presents the first combined analysis of in situ and remote observations of atmospheric tides at Mars for overlapping volumes, local times, and overlapping date ranges. From the IUVS observations, we determine the altitude and latitudinal variation of the amplitude of the nonmigrating tidal signatures, which is combined with the NGIMS, providing information on the compositional impact of these waves. Both the observations of airglow from IUVS and the CO2 density observations from NGIMS reveal a strong wave number 2 signature in a fixed local time frame. The IUVS observations reveal a strong latitudinal dependence in the amplitude of the wave number 2 signature. Combining this with the accurate CO2 density observations from NGIMS, this would suggest that the CO2 density variation is as high as 27% at 0–10° latitude. The IUVS observations reveal little altitudinal dependence in the amplitude of the wave number 2 signature, varying by only 20% from 160 to 200 km. Observations of five different species with NGIMS show that the amplitude of the wave number 2 signature varies in proportion to the inverse of the species scale height, giving rise to variation in composition as a function of longitude. The analysis and discussion here provide a roadmap for further analysis as additional coincident data from these two instruments become available. Key Points: This study presents the first simultaneous in situ and remote observations of tides at Mars The compositional impact of these waves is shown These waves produce a variation in O/CO2